Electrohydrodynamic atomization, a promising avenue for fast-dissolving drug delivery system: Lessons from tadalafil-loaded composite nanofibers - Mohammed M. Mehanna, Jana K. Alwattar, Roland Habchi (Journal of Applied Pharmaceutical Science, 2020)
The utilization of electrospinning in drug delivery has thrived in recent years, with the ability to incorporate drugs and enhance dissolution; this technique is employed to improve the dissolution of poorly water-soluble selective phosphodiesterase-5 inhibitor, tadalafil. The strategy involved direct electrospinning of tadalafil/polyvinylpyrrolidone and polyethylene oxide (PEO) solution. The optimization process included a 32 full factorial design based on the influence of polymers concentration as independent variables on the electrospun yield, loading efficiency, nanofibers diameter, number of beads, and in vitro release. Optimization studies revealed the negative influence of both polymers on the electrospun yield, while the loading efficiency and in vitro dissolution rate were reduced by the PEO concentration solely. The higher polymer concentrations were favorable for the declination of beads number, and a driving factor for fiber diameter reduction. Further physicochemical characterization of the optimized formulation revealed the presence of the drug in an amorphous state or molecular dispersion within the polymer matrix. In vitro dissolution studies revealed about 81.5% ± 8.34% release in less than 2 minutes compared to a negligible dissolution of free drug. From the derived outcomes, the electrohydrodynamic spun tadalafil-loaded nanofibers pave the way for dissolution enhancement for insoluble low bioavailability class II drugs.
Keywords: Dissolution enhancement, electrospun, factorial design, nanofiber, tadalafil, fast-dissolving drug delivery.